2011
DOI: 10.5513/jcea01/12.4.984
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin gene polymorphism in dairy cattle

Abstract: The aim of this experiment was to estimate possible associations between GHRL G375A genotypes and some milk performance traits (yields of milk, protein and fat, and protein and fat content). The study included Polish Holstein-Friesian strain Red-and-White cows. The ACRS and PCR-RFLP method was used to identification genotypes. GHRL G375A frequencies were as follow: AA-0.86, AG-0.14, and GG-was not found, while allele frequencies were: A-0.93 and G-0.07. In this study, no statistically significant correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…[4] and [5] reported that the GHLR gene expression effected significantly on milk production through the main effect on the intravenous glucose following in dairy cattle and the direct effects of ghrilin-obestatin on somatotropic axes. Other studies presented that the GHRL is the strongest stimulator of food intake in all mammalian species and the gene polymorphism in many sites is correlated strongly with variant of milk production [11,12]. The results are similar with the results of [13] who reported that the GHRL gene is considered as the main key to regulate metabolism and the functions of cardiovascular in mammals which is reflex on milk production.…”
Section: Resultssupporting
confidence: 83%
“…[4] and [5] reported that the GHLR gene expression effected significantly on milk production through the main effect on the intravenous glucose following in dairy cattle and the direct effects of ghrilin-obestatin on somatotropic axes. Other studies presented that the GHRL is the strongest stimulator of food intake in all mammalian species and the gene polymorphism in many sites is correlated strongly with variant of milk production [11,12]. The results are similar with the results of [13] who reported that the GHRL gene is considered as the main key to regulate metabolism and the functions of cardiovascular in mammals which is reflex on milk production.…”
Section: Resultssupporting
confidence: 83%
“…The authors reported that in the ghrelin gene, no significant associations were revealed between any variant sites and BW, ADG, body sizes for different growth periods (6, 12, 18, and 24 mo old), or milk yield at 305 d, milk protein rate, and milk fat percentage. Kowalewska-Łuczak et al (2011) analyzed the ghrelin gene in 169 Holstein-Friesian cows and found a G/A polymorphism on intron 3 of the gene. The authors analyzed the association of this polymor-phism with milk-production traits, but no significant differences between the genotypes were described.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have detected polymorphisms in ghrelin genes which are associated with carcass and meat quality traits in pigs [12,30], growth and feeding traits in chickens [20], growth traits in goats [31], birth weight and body length in cattle [16], and milk fat and protein synthesis in water buffaloes (Bubalus bubalis) [32]. On the other hand, some of the research results have not shown any association with phenotypes, e.g., studies on humans [33], pigs [23], cattle [34], and sheep [35]. In this study, the genotype frequency of three polymorphisms were identified: one in the promoter region (c.-93A>G) and two in the 3’UTR sequence (g.4428T>C and g.4486C>T).…”
Section: Resultsmentioning
confidence: 99%